Implikasi Teologia Postmodern Terhadap Gereja-Gereja Di Indonesia - Herdy Hutabarat (Jurnal Syntax Admiration, 2025)
The era has changed, from pre-modern to modern and now enters the postmodern era which is characterized by philosophical thinking from postmodernism which is subjective, anti-historical, pluralism of perspective and relativity. The presence of Postmodern thought is inevitable for many of humanity, including believers. These principles pose a challenge to Christian values and have an impact on the churches in Indonesia. . The influence exerted by postmodernism has also received a response from many experts. Some religious theologians and religious authority figures assert that postmodernism represents a rejection of truth. Postmodernism is one that is full of doubt, does not believe in anything, is critical and tries to look behind the surface and does not accept conventional wisdom. The response of several sociologists in Indonesia to postmodernism is generally divided into two, namely corrective and repressive attitudes. Or the question is whether Postmodern Theology is accepted or rejected? Postmodern theology offers a new perspective on understanding religion, but it also raises questions and challenges. It is important to understand both the positive and negative sides of this approach so that we can develop a deeper understanding of religion and human diversity. This article is therefore written to provide a deeper understanding of postmodernism and its implications for the Christian faith, so that it is hoped that in the future more believers will be able to give thoughtful answers and show us the attitude we should take. The results of this paper are also expected to be useful to show that Christian Theology or the Churches in Indonesia have different principles of truth from postmodernism thought and to provide a view on how the Church or believers should respond to the challenges posed by postmodernism.